2003
DOI: 10.1117/12.483980
|View full text |Cite
|
Sign up to set email alerts
|

<title>Life cycle testing of viscoelastic materials for Hubble Space Telescope solar array 3 damper</title>

Abstract: During the March 2002 Servicing Mission by Space Shuttle (STS 109), the Hubble Space Telescope (HST) was refurbished with two new solar arrays that now provide all of its power. These arrays were built with viscoelastic/titanium dampers, integral to the supporting masts, which reduce the interaction of the wing bending modes with the Telescope. Damping of over 3% of critical was achieved. 1 Figure 1. HST with Solar Array 3 (SA3) on orbit and SA3 finite element model showing damper locationTo assess the damper'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…e following two major types of control strategies have been reported in literature: the passive control methods based on viscoelastic damping materials and the active control methods based on piezoelectric materials. e implementation of passive control is easy, and its structure is simple [7,8]. Vibrations can be isolated through appropriate arrangement of damper materials at the appropriate positions of mechanisms/structures.…”
Section: Introductionmentioning
confidence: 99%
“…e following two major types of control strategies have been reported in literature: the passive control methods based on viscoelastic damping materials and the active control methods based on piezoelectric materials. e implementation of passive control is easy, and its structure is simple [7,8]. Vibrations can be isolated through appropriate arrangement of damper materials at the appropriate positions of mechanisms/structures.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1(a), this damper consists of upper and lower shear plates, and the damping layer fixes on the yoke of solar array. [5][6][7][8] The damping layer goes through shear deformation and dissipates the vibration energy due to the relative displacement between the upper and lower shear plates in the vibration process. Brugarolas et al 9 reported the structural redesign plans on this damper, as shown in Figure 1(b).…”
Section: Introductionmentioning
confidence: 99%